2006
DOI: 10.4049/jimmunol.177.5.2803
|View full text |Cite
|
Sign up to set email alerts
|

Double-Negative T Regulatory Cells Can Develop Outside the Thymus and Do Not Mature from CD8+ T Cell Precursors

Abstract: Recent studies have demonstrated that activated peripheral αβTCR+CD3+CD4−CD8−NK1.1− (double-negative, DN) regulatory T cells (Tregs) from both mice and humans are able to down-regulate immune responses in vitro and in vivo. However, the origin and developmental requirements of functional DN Tregs remain unclear. In this study, we investigated the requirement for CD8 expression as well as the presence of a thymus for the development of functional DN Tregs. We demonstrate that DN Tregs exist in CD8-deficient mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 57 publications
2
38
1
Order By: Relevance
“…Some reports suggest that DN T cells originate in the thymus by escaping negative selection [17], [18], [19]. In contrast, several reports suggest that DN T cells are generated in the periphery rather than in the thymus [19], [20], [21], [22]. These cells comprise about 1–5% of total T cells in non-transgenic mice and in humans [11], [23] making them difficult to isolate and subsequently study.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggest that DN T cells originate in the thymus by escaping negative selection [17], [18], [19]. In contrast, several reports suggest that DN T cells are generated in the periphery rather than in the thymus [19], [20], [21], [22]. These cells comprise about 1–5% of total T cells in non-transgenic mice and in humans [11], [23] making them difficult to isolate and subsequently study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that they originate through a thymus-independent process (5,6). However, several lines of evidence strongly support the hypothesis that DN T cells arise from activated thymic-derived CD4 + (7,8) or CD8 + cells (9-11).…”
Section: Introductionmentioning
confidence: 99%
“…In murine transplantation models, conventional DNT cells have been shown to suppress immune responses through Fas/FasL-mediated elimination of effector T cells [48][49][50][51][52][53] Of interest, DNT cells from MRL/lpr mice, a murine model of ALPS, were shown to kill syngeneic wild-type, but not Fas-deficient, lpr CD4 1 or CD8 1 T cells, indicating that the regulatory function of DNT cells in lpr mice is retained. 48 We demonstrated recently that activation of the mTOR pathway abrogates the immunoregulatory function of DNT cells from healthy volunteers by reversing their anergic phenotype while promoting proliferation.…”
Section: P-aktmentioning
confidence: 99%